2009
DOI: 10.1007/s11845-009-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Irish youth: epidemiology and implications

Abstract: The worldwide epidemic of type 2 diabetes has been paralleled by a marked increase in the prevalence of obesity, particularly in younger people. This will contribute significantly to the future burden of cardiovascular disease. Complex environmental and genetic factors contribute to obesity and related metabolic disorders. These disorders are now manifesting in younger age groups, including children. Recent studies have described the clinical and metabolic characteristics of these children. A solution to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…For example, one study reported that the variation in androgen levels immediately after weight loss in obese women with regular menstrual cycles is due to the sustained increase in SHBG after weight loss, which leads to the decrease of free testosterone (26,27). This androgen insufficiency is associated with reduced sexual desire.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported that the variation in androgen levels immediately after weight loss in obese women with regular menstrual cycles is due to the sustained increase in SHBG after weight loss, which leads to the decrease of free testosterone (26,27). This androgen insufficiency is associated with reduced sexual desire.…”
Section: Discussionmentioning
confidence: 99%
“…3,[40][41][42] Androgen insufficiency is associated with hypoactive sexual desire disorder, 43 and androgen, in contrast, can increase sexual desire, arousal, orgasm and satisfaction. 44,45 Weight reduction, therefore, can reduce the score in each of these domains.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30% of adults in some of the states are now obese. 3 In the 2003-2004 time period, the prevalence of obesity among adults was 32.2%. 4 Increasing trends in obesity cause concern among health authorities in terms of associated co-morbidities, including type II diabetes, heart disease, hypertension and certain cancer types.…”
Section: Introductionmentioning
confidence: 99%